(untitled) (Periphērica, 2020)
This essay analyzes the representation of female activism in La mujer metralleta, a documentary by Chilean Francisco López Balló that reconstructs the biography of Marcela Rodríguez Valdivieso, a guerrilla who has succumbed to the oblivion in Chile. It is necessary to highlight her anti-dictatorial fight in order to recover her name and that of so many other militants. My study aims to eliminate the prevailing silence around the exiles who also contributed to the redemocratization processes in Chile and participated in the resistance against Pinochet. Despite their constant political activism, women have been excluded from official historiography. This essay claims a place in the world to one of the many activists who experienced the process of Chilean exile and whose biography contributes to a better understanding of female activism. This documentary offers a new approach to the past is constructed that questions the relations between the State and the revolutionary position of women, despite the fact that women have historically played a marginal role in war conflicts. My paper points out the relevance of this guerrilla, how this documentary contributes to reconstructing history and how exile affects the transmission of memories.